Narzędzia, instrumenty z powiatowych urzędów pracy ułatwiające funkcjonowanie przedsiębiorstw w warunkach pokryzysowych - Nowogrodzka, Monika (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2016)
The purpose of this article is to present the most important forms of support offered by the District Labor Offices, which the entrepreneur can benefit from in the conditions of crisis and post-crisis. The subject matter was developed mainly on the basis of the law on employment promotion and labor market institutions. Outlined are the principles of obtaining funds from the PUP and membership benefits for the entrepreneur. The article refers in particular to: a grant for opening a business by the unemployed, apprenticeships for the unemployed, intervention works, reimbursement of the cost of equipment or retrofit jobs position and the National Training Fund. The work was written based both on professional literature and on the basis of their own experience with the acquisition of the above measures.
Keywords: grants; the district labor office; internships; public finances; The National Training Fund; act on employment promotion and labor market institutions; forms of support; intervention works